A 40-GHz Colliding Pulse Mode-Locked Semiconductor Laser*Supported by the National Natural Science Foundation of China under Grant Nos 61335009, 61274046 and 61474111. (June 2016) - Liu 刘, Song-Tao 松涛; Zhang 张, Rui-Kang 瑞康; Lu 陆, Dan 丹; Kan 阚, Qiang 强; Wang 王, Wei 圩; Ji 吉, Chen 晨
Abstract : A monolithically active-passive integrated colliding pulse mode-locked semiconductor laser is demonstrated in the InGaAsP/InP material system. The device is mode locked at the second harmonic passive mode-locking regime with a wide mode-locking range. Pulse trains with the repetition rate of 40 GHz, 3-dB rf line width of 25 kHz, the pulse width of 2.5 ps, and a nearly transform-limited time-bandwidth product of 0.53 are obtained.